Annotated list and key to the stream fishes of Trinidad & Tobago - Phillip, Dawn A.t.; Taphorn, Donald C.; Holm, Erling; Gilliam, James F.; Lamphere, Bradley A.; López-Fernández, Hernán (Zootaxa, 2013)
Based on historical and museum records and recent extensive collecting we compiled a checklist of 77 fish species reported from the streams of Trinidad and Tobago. A key with photographs is provided to aid in identifications, as well as brief notes on habitat, diet, reproduction, maximum size, local common names and distribution.